"It's a Man Thing, Gina": Watching Gender in Martin. (23rd February 2021) - Johnson, Patrick
Abstract: In the almost three decades since the hit situation-comedy Martin (1992–1997) originally aired on Fox, the show has not only enjoyed a vibrant second life through syndication and streaming platforms, but has functioned as a form of television heritage, reflected in fashion, music, games, and memes. Martin has developed a particularly loyal following among black millennials, many of whom were too young to watch the show during its original network television run. In this article, I explore the series' representations of black women through individual and focus group interviews with 26 black viewers. My interviews reveal that participants have ambivalent relationships with the show. While several cite Martin as their favorite show of all-time, they were disturbed by the show's troubling depictions of black heterosexual romantic relationships and its reliance on stereotypical representations of black women.